Risk Analysis of Pemalang District Road and Bridge Construction Delays - Citra Pradipta Hudoyo; Iwan Rustendi; Ika Handayani (POLITEKNIK NEGERI JAKARTA, 2023)
Delays in road and bridge construction projects pose significant challenges within the construction industry. These delays can be attributed to various risk factors that have the potential to disrupt project timelines. This study focuses on identifying the risk factors that contribute to delays in road and bridge construction projects in the Pemalang district. A comprehensive review of relevant literature was conducted to identify these risk factors, which were then incorporated into questionnaires distributed among contractors, owners, and consultants. The questionnaire data was analyzed using the mean score ranking method, along with validity and reliability tests, and descriptive statistical analysis facilitated by the SPSS program. The research findings unveiled a total of 54 risk factors categorized into 11 distinct categories. Among these, the top 10 causes of delays in road and bridge construction projects in the Pemalang district were identified based on mean values ranging from 4.18 to 4.57. These factors encompassed issues such as shortages of construction materials (4.57), delays in goods delivery (4.48), equipment delivery delays (4.40), difficulties in contractor funding (4.37), inadequate workforce or inability to meet project demands (4.37), rainfall intensity (4.35), poor material quality (4.30), ordering time inaccuracies (4.27), insufficient skilled labor (4.23), and equipment damage (4.18). Furthermore, interviews were conducted with experts to discuss the 10 risk factors with the highest impact. Strategies to mitigate these risks were derived from these discussions. The outcomes of this research are anticipated to provide valuable insights for stakeholders involved in the planning and execution of road and bridge construction projects. By understanding the underlying risk factors and implementing the recommended strategies, it is expected that project delays can be significantly reduced in future endeavors.